Analysis of Implementation of Branching Method in ODP in Fiber to The Home using Optisystem Case Study PT. MGN CORP - Darsono, Novaldy Bagus; Anshori, Moh. Abdullah; Hudiono, Hudiono (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Fiber to the Home (FTTH) deployment efficiency critically depends on the Optical Distribution Point (ODP) installation method. Traditional closure-based branching requires precise and labor-intensive fiber splicing. This study analyzes an alternative branching method implemented directly at the ODP using passive splitters and drop cables, eliminating the need for field splicing. The research, conducted as a case study at PT. MGN CORP and simulated in Optisystem, evaluates a cascaded splitter architecture: a 1:4 splitter output from the Optical Distribution Cabinet (ODC) is connected to a 1:8 splitter at the ODP. Two ODP types—Pedestal and Pole—were tested. Results show downstream attenuation values of 18.93 dB for the Pedestal ODP and 19.03 dB for the Pole ODP at the customer premises, both compliant with the ITU-T G.984 standard. The analysis confirms a direct correlation between the ODC-ODP distance and link attenuation. The proposed method simplifies field installation, reduces deployment time and skill dependency, and maintains requisite signal quality, offering a viable solution for scalable and cost-effective FTTH network rollout.